Antibacterial Activity of Endophyte Fungus from Sambiloto Flowers (Andrographis paniculata) on Black Rice Growing Media - Rizka Purwanti; Iryani Iryani; Riga Riga; Mariam Ulfah (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Sambiloto plant (A. paniculata) is widely reported to have secondary metabolites that act as antibacterial. The potential is not only derived from the natural A. paniculata plant but can also be explored from its endophytic fungus. This study aimed to determine the antibacterial activity of ethyl acetate extract of endophytic fungus BS isolated from bitter flower (A. paniculata) on black rice growing media against Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa bacteria. The antibacterial activity test of the extract was carried out by disc diffusion method. The results obtained showed that the ethyl acetate extract of BS endophytic fungus grown on black rice media showed activity to inhibit the growth of Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa bacteria at concentrations of 10%, 30%, and 50%. In conclusion, the ethyl acetate extract of the endophytic mushroom BS isolated from the bitter flower (A. paniculata) can be used as an antibacterial.